1987
DOI: 10.1038/icb.1987.54
|View full text |Cite
|
Sign up to set email alerts
|

CR3 receptor on platelets and its role in the prostaglandin metabolic pathway

Abstract: Summary. The human C3R receptor, which binds C3bi, present on the surface of monocytes, granulocytes and natural killer cells, can be detected by several monoclonal antibodies, OKMI, Mol and Mac-1 and also by RM2.I84 which detects a polymorphism of the receptor. Platelets have been considered to lack complement receptors on their cell surface; however, we now describe the detection of CR3 receptors on human platelets by radioimmunoassay using both OKMI and RM2.184 antibodies. Using OKMI, immunoprecipitation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…12,21 The opsonin iC3b binds to these cells via CR3 (the integrin receptor CD11b/CD18). 22,23 We have shown the presence of C3c, iC3b, C3b, C9, and C5b-9 on the platelet surface, particularly after stimulation with Stx2 and O157LPS. Microparticles released from cells during apoptosis and activation 24 may bind complement components such as C1q, C3, and C4.…”
Section: Discussionmentioning
confidence: 99%
“…12,21 The opsonin iC3b binds to these cells via CR3 (the integrin receptor CD11b/CD18). 22,23 We have shown the presence of C3c, iC3b, C3b, C9, and C5b-9 on the platelet surface, particularly after stimulation with Stx2 and O157LPS. Microparticles released from cells during apoptosis and activation 24 may bind complement components such as C1q, C3, and C4.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in experimental animal models, platelets intensify at sites enriched in microbial stimuli such as N -formyl-methionyl-leucyl-phenylalanine ( N - f -met-leu-phe) [29] or complement proteins C3a and C5a [1, 7, 25, 30]. Experiments by Czapigaa et al .…”
Section: Platelets: the Other White Cellsmentioning
confidence: 99%
“…For example, platelets and professional phagocytes such as neutrophils and monocytes share common surface antigens: the 40-kDa FcγRII receptor [21], FcεRI receptor for IgE [22], C-reactive protein receptor [23], and the thrombospondin receptor CD36 (platelet GPIV) [24]. Platelets also express complement CR3 receptor [25], receptors for C3a and C5a products of complement fixation, and sense and respond to cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1), and IL-6 in a manner similar to leukocytes [26, 27]. Clemetson et al [28] reported that human platelets express functional chemokine receptors, including CCR1, CCR3, CCR4, and CXCR4.…”
Section: Platelets: the Other White Cellsmentioning
confidence: 99%
“…Immunofluorescent staining of late inclusions (36 hr after infection) with mAb 12k1 did not stain the EBs, indicating that the Hcl antigenic epitope was not accessible to antibody on intact chlamydiae. Interestingly, mAb 12k1 stained the nucleus of infected and uninfected HeLa cells with a pattern reflective of antibodies to H1 histone (22) (Fig. 5) (24).…”
mentioning
confidence: 99%